Mergers and Acquisitions in Brazilian Higher Education Companies: Effect on Share Value - Silva, Alan Willame de Souza; Junior, Tabajara Pimenta; Soares, Mara Alves; Gaio, Luiz Eduardo; Ambrozini, Marcelo Augusto (Finance & Economics Review, 2021)
Purpose: The objective of this study is to detect and measure the occurrence of extraordinary returns to the shareholders of private higher education companies, listed on the Brazilian stock market, B3, when mergers and acquisitions occur. Methods: This study uses the Event Study technique on process data from 46 merger and acquisition events, that occurred in the period of 2007- 2015, involving the three main Brazilian private higher education companies, and applies the Z-statistic to test the accumulated standard abnormal returns. Results: Based on the results, it is possible to affirm that the presence of abnormal returns was not detected after merger and acquisition events. Events of this nature do not promote changes in the short-term value of the company, in the cases of large and publicly traded Brazilian private higher education companies. Implications: The announcement of a merger or acquisition process has wide repercussions in the media and attracts the attention of investors that aims to gain abnormal earnings from anticipated post-merger value creation. This study showed that the potential gain in value does not always occur or is reflected in the stock prices of the companies involved, in the short term.